Memodifikasi Wedang Kacang Menjadi Panna Cotta Wedang Kacang sebagai Fussion Dessert - Yonatan Kristiawan; Suparwi Suparwi; Dewi Hermawati Wahyuningsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to develop an innovative dessert product called Panna Cotta Wedang Kacang that combines Italian culinary elements with traditional Indonesian flavors. Panna cotta, a classic Italian dessert made from milk and gelatin, is creatively infused with wedang kacang, a traditional Javanese beverage consisting of sweet ginger broth and boiled peanuts, to create a unique taste sensation that reflects local cultural values. This study employs a Research and Development (R&D) method with an experimental approach to determine the best formulation based on organoleptic aspects, namely taste, aroma, texture, and appearance. Organoleptic testing was conducted with 30 panelists using a 1–5 hedonic scale. The results indicate that the optimal formulation is achieved from a combination of panna cotta made with liquid milk, cream, sugar, gelatin, and wedang kacang broth in a 2:1 ratio, topped with boiled peanuts. The final product received the highest scores for taste and aroma, particularly due to the harmonious blend of the creamy mild flavor of panna cotta and the warm sweetness of ginger from the wedang kacang. Additionally, the nutritional content of the product was analyzed descriptively, demonstrating that Panna Cotta Wedang Kacang has the potential to serve as a functional dessert due to its plant-based protein and antioxidant content from ginger. The conclusion of this research is that Panna Cotta Wedang Kacang is well-received by consumers and has the potential to be developed as a modern dessert alternative with a local touch.